(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The purpose of this paper is to introduce the probabilistic multiple poly Bernoulli polynomials of the second kind under the condition that Y is a random variable. This means that we will consider the probabilistic extension of the multiple poly Bernoulli polynomials of the second kind and study to obtain some new results. Furthermore, we investigate their interesting properties.